2016
DOI: 10.4155/bio.16.17
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Ultra-Sensitive Simoa Assay to Enable Gdf11 Detection: A Comparison Across Bioanalytical Platforms

Abstract: This improvement was essential to enable detection of GDF11 in biological samples, and without the technology the sensitivity achieved on the other platforms would not have been sufficient. Other factors such as ease of use, cost, assay time and automation capability can also be considered when developing custom immunoassays, based on the requirements of the bioanalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nano/microbeads have also been used in highly sensitive and multiplexed commercial applications, such as Dynabeads [211,249,255] and digital ELISAs (dELISA), also known as single molecule array (SiMoA) [260,261]. dELISA can trap and detect single proteins in femtolitersized wells [262,263].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Nano/microbeads have also been used in highly sensitive and multiplexed commercial applications, such as Dynabeads [211,249,255] and digital ELISAs (dELISA), also known as single molecule array (SiMoA) [260,261]. dELISA can trap and detect single proteins in femtolitersized wells [262,263].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…While a handful of studies have demonstrated superiority of Simoa compared to standard ELISA in these respects, very few have compared MSD HPE to Quanterix Simoa. In one study, Myzithras and colleagues found Simoa achieved higher sensitivity detecting a growth factor (GDF11), a 100-fold improvement in the lower limit of quantification compared to MSD, in standardized pooled samples 11 . Another study demonstrated that use of CSF AB42/Ab40 ratios as quantified on HPE or Simoa were comparably sensitive in classifying abnormal amyloid PET 12 .…”
Section: Introductionmentioning
confidence: 99%